Speech Styles used by Teacher Characters in Education-themed Movies - Veni Theresia Kedoa; Ika P Lantu (Sintuwu Maroso Journal of English Teaching, 2018)
This research aims to analyze the speech style of the teachers in movies. The theories that were applied in this research are Joos theory (1967) which concern about speech style, and also the theory of context from Hymes (1975) that influences the speech style (SPEAKING). Design of this research is descriptive qualitative. The instrument of collect the data use the transcript of three movies they are Dead Poets Society, Dangerous Minds, and Freedom Writers. The result ofthis research shows that the most dominant speech style used by the teachers inmovies is consultative style and the teachers used this style since they want to giveopportunity to the students to participate in learning process.Keywords: consultative speech style, teacher characters, education-themedmovies